PENGARUH CITRA RUMAH SAKIT DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PASIEN MELALUI KEPUASAN PASIEN (STUDI PADA RUMAH SAKIT UMUM KARDINAH TEGAL) - M. Andi Ardiyanto; Mr. Tabrani (Program Studi Magister Manajemen, Universitas Pancasakti Tegal - Indonesia, 2018)
M. Andi Ardiyanto. Influence of Image and Quality of Service To Consumer Loyalty Through Consumer Satisfaction (Study At Hospital KardinahTegal). Thesis.Tegal: Master of Management Pancasakti University of Tegal. 2017 The purpose of this research is to test empirically the influence of image and service quality to consumer loyalty through consumer satisfaction (Study AtHospital KardinahTegal). The research variables in this research are image, service quality, satisfaction and loyalty. The hypothesis of this study is the image and quality of service influence on consumer loyalty through consumer satisfaction. Data collection method used in this research is questionnaire. While the data analysis method used is SEM analysis using AMOS application The result of this research are (1) image have positive effect to satisfaction (2) service quality have positive effect to satisfaction (3) image have positive effect to loyalty (4) service quality have positive influence to loyalty (5) satisfaction positive effect to loyalty (6) Can mediate the influence of the image on loyalty but satisfaction can not mediate the influence of service quality on loyalty.Keywords: Image, Service Quality, Satisfaction, Loyalty